2018
DOI: 10.1093/jas/sky248
|View full text |Cite
|
Sign up to set email alerts
|

Anogenital distance reflects the sex ratio of a gilt’s birth litter and predicts her reproductive success1

Abstract: Anogenital distance (AGD) has been used to reflect masculinization in litter-bearing species. As masculinization affects behavior and reproduction, AGD could be measured to assist in selecting gilts with a temperament more suited to commercial production and greater reproductive potential. We hypothesized that gilts from a male-biased litter would have a longer AGD and poorer reproductive performance. In Exp. 1, AGD and weight were measured at day 1, day 21, and week 16 of age for gilts from male-biased litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Drickamer et al [38] reported that gilts originating from a male-biased litter (>67% males) had a larger anogenital distance when measured within four days after birth as compared with gilts from litters with lower proportions of males in the litter. In contrast, Seyfeng et al [36] reported that although anogenital distance was not different between male-biased (>60% males) as compared with female-biased (>60% females) litters at day one of age, gilts from female-biased litters had a longer anogenital distance at three and 16 weeks of age. In a second study by the same authors, anogenital distance was measured at the time of preselection at approximately 170 days of age.…”
Section: Birth Traits That Determine the Efficiency Of Replacementmentioning
confidence: 94%
See 4 more Smart Citations
“…Drickamer et al [38] reported that gilts originating from a male-biased litter (>67% males) had a larger anogenital distance when measured within four days after birth as compared with gilts from litters with lower proportions of males in the litter. In contrast, Seyfeng et al [36] reported that although anogenital distance was not different between male-biased (>60% males) as compared with female-biased (>60% females) litters at day one of age, gilts from female-biased litters had a longer anogenital distance at three and 16 weeks of age. In a second study by the same authors, anogenital distance was measured at the time of preselection at approximately 170 days of age.…”
Section: Birth Traits That Determine the Efficiency Of Replacementmentioning
confidence: 94%
“…The sex ratio of the litter where the replacement female was born may affect lifetime performance and behavior and could potentially be used as another selection tool at birth [34,35]. Gilts born to litters with a high proportion of males are exposed to increased levels of androgens from their male littermates in utero causing gilts to become masculinized [34,36]. It is generally reported that gilts born in female-biased litters are potentially better replacement females than gilts from male-biased litters, however, more research in this area is needed [34].…”
Section: Birth Traits That Determine the Efficiency Of Replacementmentioning
confidence: 99%
See 3 more Smart Citations